(3TQM GdKdGKjf eSFdIs - (3GdUGMHjs
(3ChdgG (B:s
(3HOC GdTjN HGdJSejI abGd HSe Gddg GdQMef GdQMje hGdcdGe efg jbY ai KdGKI ehGVY GdChd ai hLg GdHOGjI Hg s
(3BNQgG (B:s
(3ajLH Ydi cd ecda Cf jfXQ ai UMI Ojfg afSCd Gddg Cf jLYdfG ef GdPjf jSJeYhf Gdbhd ajJHYhf CMSfg ChdFc GdPjf hGdSdGe Ydi ef GJHY GdgOi hddCNQg NjQ dc ef GdChdi hEf Edi QHc GdefJgi s
(3HgG fXGe GdJYbjHIs
(3cJHJ HYV GdcdeGJ HGdMeQIs
(3eUOQ GbJfGA GdCUd (B:s
(3GdaGJjcGf s
Keywords: (3GdeYGQa GdYGeIs